1988
DOI: 10.1002/ijc.2910420623
|View full text |Cite
|
Sign up to set email alerts
|

Changes in in vitro growth behaviour of the mammary epithelial cell line NMuMG caused by the v‐fos oncogene

Abstract: A defective retrovirus was constructed to investigate the effect of the expression of the v‐fos oncogene from FBJ‐MSV on the in vitro growth properties of the mammary epithelial cell line NMuMG. Clearly visible areas of overgrowth in monolayer cultures of NMuMG were seen in cells infected with the v‐fos‐containing retrovirus but not in cells infected with control virus which did not contain an oncogene. Two cell lines, representing two morphological types of infected cell, were isolated from a morphologically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Cells transformed by accumulated genetic mutations proliferate and push out surrounding nontransformed cells, forming a cell mass called a focus in vitro . Focus formation assays utilizing this property have been widely used to identify oncogenes ( 5 ). We previously established a focus formation assay using normal mouse mammary epithelial cells (NMuMG) and identified several novel oncogenes ( 6 , 7 , 8 ).…”
mentioning
confidence: 99%
“…Cells transformed by accumulated genetic mutations proliferate and push out surrounding nontransformed cells, forming a cell mass called a focus in vitro . Focus formation assays utilizing this property have been widely used to identify oncogenes ( 5 ). We previously established a focus formation assay using normal mouse mammary epithelial cells (NMuMG) and identified several novel oncogenes ( 6 , 7 , 8 ).…”
mentioning
confidence: 99%
“…Northern analysis of the #43raf lines showed only one detectable transcript, but was not able to exclude expression from rearranged proviruses. Rearrangement of retroviral vectors has frequently been observed (Laker et al, 1987;Bradbury and Edwards, 1988;Gonda et al, 1989). In our hands, both YR and MPSVneo have shown a tendency to rearrange, an instability which should be considered when these or similar vectors are used.…”
Section: Discussionmentioning
confidence: 93%
“…We chose oncogenes which might have been expected to affect mammary epithelium. Previous reports have shown that some oncogenes cause easily observed morphological changes in certain types of epithelial cell (Fusco et al, 1985;Bradbury and Edwards, 1988;Giinzburg et al, 1988) while others do not (Giinzburg et al, 1988;Redmond et al, 1988). In the work reported here, both rufand rnos altered the morphology of the mammary epithelial cell line #43, and infected polyclonal cultures showed distinct areas of multilayering.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations